2018
DOI: 10.1007/s00277-017-3223-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of advanced glycation end products positively correlate with iron overload and oxidative stress markers in patients with β-thalassemia major

Abstract: The impaired biosynthesis of the β-globin chain in β-thalassemia leads to the accumulation of unpaired alpha globin chains, failure in hemoglobin formation, and iron overload due to frequent blood transfusion. Iron excess causes oxidative stress and massive tissue injuries. Advanced glycation end products (AGEs) are harmful agents, and their production accelerates in oxidative conditions. This study was conducted on 45 patients with major β-thalassemia who received frequent blood transfusions and chelation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It has long been recognized that genetic iron overload can lead to male hypogonadism [15]. A recent clinical study conducted by Mirlohi et al reported that serum AGEs were positively correlated with iron overload and markers of oxidative stress in patients with ß-thalassemia major [37]. As far as we are aware, mechanisms underlying iron-mediated endogenous AGE formation, trapping, and clearance are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recognized that genetic iron overload can lead to male hypogonadism [15]. A recent clinical study conducted by Mirlohi et al reported that serum AGEs were positively correlated with iron overload and markers of oxidative stress in patients with ß-thalassemia major [37]. As far as we are aware, mechanisms underlying iron-mediated endogenous AGE formation, trapping, and clearance are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies investigated the effects of iron on AGEs metabolism. In 2018, Mirlohi et al [37] first reported that plasma levels of CML and pentosidine (PTD) were increased in the patients with β-thalassemia major, and serum PTD, not CML, were positively correlated with markers of iron overload (serum ferritin, iron). Early in vitro studies showed that CML is formed during copper-catalyzed oxidation of polyunsaturated fatty acids in the presence of protein [38] and the formation of CML is suppressed by the addition of iron chelator desferrioxamine or iron-containing ant-oxidative enzymes such as catalase and superoxide dismutase (SOD2) [39].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the poten-tial catalytic role of Fe 2+ in the formation of AGEs in type 1 collagen has been clearly demonstrated [96]. In patients with β-thalassemia major, serum iron and especially non-transferrin-bound iron are typically elevated, and a positive correlation has been reported between this elevation and AGE (carboxymethyl-lysine and pentosidine) concentrations [97]. Correspondingly, in our recent experimental study Fe supplementation in obese rats induced a significant accumulation of AGEs and especially of CML in the liver [98].…”
Section: Glycation and Age Toxicity In Ad As Influenced By Fementioning
confidence: 97%
“…Mirlohi et al 32 found that level of advanced glycation end products was affected by iron overload, patients with β-thalassemia may lead to higher advanced glycation end products, which suggest iron status may affect protein glycation. This let us hypothesize that the effect of ferritin on disassociation of HbA1c and MPG may be not only dependent on the impact of ferritin on life cycle of erythrocytes, but abnormal iron status may influence the glycation rate of hemoglobin and albumin; further investigation needs to be carried out to understand this.…”
Section: Discussionmentioning
confidence: 99%